The effects and pollution control of wood preservation chemicals / Azimah Husain - Husain, Azimah (2004)
This review is to survey the effects and pollution control of wood preservation chemicals. Generally, the purposes of wood preservation are to preserve the structural integrity and extend the lifetime of wood. But its use may be able to bring effects to public health and environment especially if the treated wood is not properly used and handled. However, the effects and pollution of wood preservation chemicals will be prevented when suitable and effective steps were taken.